2019
DOI: 10.1016/j.wear.2019.202959
|View full text |Cite
|
Sign up to set email alerts
|

2D and 3D characterization of rolling contact fatigue cracks in manganese steel wing rails from a crossing

Abstract: Rail wheel contact at switches and crossings (S&Cs) induces impact stresses along with normal and shear contact stresses, resulting in plastic deformation and eventually crack formation. Damaged and deformed wing rails of a manganese steel crossing are studied and the microstructure, hardness and 3D crack network within the steel are characterized. The surface of the rail receives the maximum deformation resulting in a hardened top layer. The deformation is manifested in a high density of twins and dislocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For the same reason, it is unlikely that a single cavitation event in lubricant film between metal surfaces could be observed, but time-averaged distributions of vapour fractions in macroscopic cavitating flows have been collected successfully [52,53,54] using x-ray computed tomography. As demonstrated by previous work [24,20,17,22,23], x-ray tomography is capable of resolving subsurface cracks. Use of x-ray tomography in wear studies can therefore be extended to observe not only the development of the contact region, but also the material around it, which could be beneficial in studies of wear-induced cracking.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…For the same reason, it is unlikely that a single cavitation event in lubricant film between metal surfaces could be observed, but time-averaged distributions of vapour fractions in macroscopic cavitating flows have been collected successfully [52,53,54] using x-ray computed tomography. As demonstrated by previous work [24,20,17,22,23], x-ray tomography is capable of resolving subsurface cracks. Use of x-ray tomography in wear studies can therefore be extended to observe not only the development of the contact region, but also the material around it, which could be beneficial in studies of wear-induced cracking.…”
Section: Discussionmentioning
confidence: 76%
“…In combination with particle tracking, X-ray tomography has been used to observe and study Couette flow of granular materials [16] in-situ. Several ex-situ CT studies of wear and/or rolling fatigue cracks are reported [17,18,19,20,21]; in-situ investigations of tribo-fatigue-induced cracking in metals have also been performed successfully [22,23,24], enabling the growth of fatigue cracks to be visualized. X-ray tomography has also been used to study frictional welding: Steuwer et al [25] studied the morphology of weld inclusions resulting from wear of friction stir welding tools, while Cornuault & Carpentier [26] obtained post-weld tomographs of the welded zone in linear friction welds.…”
Section: Introductionmentioning
confidence: 99%